PENGARUH BOARD STRUCTURE DAN OWNERSHIP STRUCTURE TERHADAP EARNINGS VARIABILITY MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI - Cynthia Aggrean; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aims to examine the direct effect between the board structure on earnings variability, ownership structure to earnings variability, and impact of intellectual capital disclosure to earnings variability. In addition, this study also aims to determine the indirect influence between the board structure and ownership structure on earnings variability through intellectual capital disclosure as a mediation variable. The sample used in this research are 72 manufacturing companies listed on Indonesia Stock Exchange with observation year from 2010-2015. Data is collected from the company's annual report and processed using WarpPLS version 5.0 software.The result of the research found negative impact of board structure to intellectual capital disclosure, negative impact of ownership structure to intellectual capital disclosure, negative impact of board structure to earnings variability, no impact of ownership structure to earnings variability, and negative impact of intellectual capital disclosure to earnings variability. In addition, the study also found that intellectual capital disclosure has failed to become a mediation variable toward the impact of board structure and ownership structure on earnings variability.